Wiest, Karin (ed.) (2016). Women and Migration in Rural Europe. Labour Markets, Representations and Policies - Solé, Aimada (Documents d'Anàlisi Geogràfica, 2018)
Wiest, Karin (ed.) (2016) Women and Migration in Rural Europe. Labour Markets, Representations and Policies Nova York: Palgrave Macmillan, 257 p. ISBN 978-1-137-48304-1